Перерозподіл газу між об'ємною та бульбашковою фазою у воді, що опромінена електромагнітними хвилями низької інтенсивності - Алмазова, Олена Борисівна; Лисиченко, Микола Леонідович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Одержано, що опромінення рідкої води електромагнітними хвилями низької інтенсивності сантиметрового діапазону забезпечує зростання вільного повітря, що міститься у воді. Це збільшення викликане перенесенням у бульбашки частини газу, що розчинений у воді. "Бульбашковим" механізмом можна пояснити ефекти впливу низькоінтенсивних електромагнітних хвиль на біологічні рідини.

It has been established that the irradiation of liquid water with low-intensity electromagnetic waves of the centimeters range provides: 1. Increasing the amount of light scattering (and optical density) of the water sample. 2. An increase in the volume of free air contained in the water. These changes are due to the transfer of part of the gas dissolved in water into air bubbles. The mechanism "bubble" can explain the effects of low-intensity electromagnetic waves on biological fluids. Also, a change in the "standard" mode of functioning of a living cell.
Redistribution of gas between the bulk and bubble phases in water irradiated with low-intensity electromagnetic waves
Keywords: електромагнітні хвилі; опромінення; повітряні бульбашки; electromagnetic waves; irradiation; air bubbles